Janus kinase inhibitors vs. abatacept about safety and efficacy for patients with rheumatoid arthritis-associated interstitial lung disease: a retrospective nested case-control study - Atsuko Tsujii; Kentaro Isoda; Maiko Yoshimura; Akihiko Nakabayashi; Dong-Seop Kim; Tatsuya Tamada; Kurumi Yamamoto; Shiro Ohshima (BMC Rheumatology, 2024)
Abstract Background Interstitial lung disease (ILD) related to rheumatoid arthritis (RA) is among the leading causes of death and an essential prognostic factor. There is only limited evidence for the safety of anti-rheumatic drugs for patients with RA-ILD. The aim of this study is to investigate the safety and efficacy of Janus kinase inhibitors (JAKis) by comparing it with abatacept (ABT) in patients with RA-ILD. Methods This single centre, retrospective nested case–control study enrolled patients with RA-ILD treated with JAKi or ABT. To determine the safety of the two drugs for existing ILD, we compared their drug persistency, incidence rates of pulmonary complications, and change of chest computed tomography (CT) image. For their efficacy as RA treatment, disease activity scores and prednisolone (PSL)-sparing effect were compared. We performed propensity score matching to match the groups’ patient characteristics. Results We studied 71 patients with RA-ILD (ABT, n = 45; JAKi, n = 26). At baseline, the JAKi group had longer disease duration, longer duration of past bDMARD or JAKi use and higher usual interstitial pneumonia rate. After propensity score matching, no significant differences in patient characteristics were found between the two groups. No significant difference in the drug persistency rate for the first 2 years (ABT, 61.9%; JAKi, 42.8%; P = 0.256) was observed between the two matched groups. The incidence rate of pulmonary complications did not differ significantly between the two groups (P = 0.683). The CT score did not change after the treatment for the ABT group (Ground-glass opacities (GGO): P = 0.87; fibrosis: P = 0.78), while the GGO score significantly improved for the JAKi group (P = 0.03), although the number was limited (ABT: n = 7; JAKi: n = 8). The fibrosis score of the JAKi group did not change significantly.(P = 0.82). Regarding the efficacy for RA, a significant decrease in disease activity scores after the 1-year treatment was observed in both groups, and PSL dose was successfully tapered, although no significant differences were observed between the two drugs. Conclusions JAKi is as safe and effective as ABT for patients with RA-ILD. JAKi can be a good treatment option for such patients.